Bentuk Kias Berunsur Tangan dan Aktivitas dengan Tangan pada Korpus Digital - Ummu Latifah; M, Rawinda Fitrotul; Prayogi, Icuk (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2024)
The role of language as a communication tool is very important because it carries messages and provides information from the speaker or to the interlocutor. One of the uses of language to convey messages is by using hand activities. The research aims to analyze forms of figurative expressions involving the hand, specifically the use of figurative language and expressions that correlate with body parts, with the object being the Digital Corpus. The research approach used in this study is a qualitative approach through descriptive exposition. The methodological steps will be elaborated by the researcher through observation, analysis process, and description. Based on the analysis results, it can be concluded that, first: In the digital corpus CQPweb Lancaster University, a total of 91 figurative expressions involving the hand and hand activities were found. Second: In the process of forming figurative expressions involving the hand, only morphological processes of blending or composition in meaning formation were found. Third: The internal relation in figurative expressions involving the hand is formed by the arrangement or elements of two words that form a compound word. These compound words then indicate figurative meaning. This figurative meaning is produced from the combination of the meanings of the two combined words. Fourth: Several functions of figurative expressions involving the hand include: (1) creating poetic effects, (2) conveying implied meanings, (3) creating cultural identification, (4) creating expressive meanings, and (5) creating social and political critique.